ANALISIS PELAKSANAAN MANAJEMEN ASET TETAP (TANAH DAN BANGUNAN) DAN STRATEGI PENINGKATAN PELAKSANAAN MANAJEMEN ASET PEMERINTAH DAERAH KABUPATEN NIAS - , Yenni Mulianti Lase ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aimed to analyze the implementation of asset management in Local Government of Kabupaten Nias and how the strategy should be done to enhance the implementation of asset management. The implementation of asset management measured through the importance and performance using the IPA (Importance Performance Analysis) is to measure the level of importance and performance. (Martilla and James, 1977). However, the implementation asset management enhancement was done by using the SWOT analysis. This research was also use the Kruskall Wallis to find the difference of perceptions of the importance level and performance among managements. This research was using the purposive sampling technique with 78 samples of respondents. The result shows that the inventory consist of data collecting, data recording, and the information storing related to land and buildings assets that have the highest importance level with mean 4,59 and modus 5 (very important). Furthermore, the result of the highest of performance level was the legal strategic plan of land and building assets procurements that integrated with the local government goals and have the mean value 4,08 and modus 4 (good). The Kruskal Wallis test shows that there was not any perception difference on the importance level among the managements